Factors Influencing Repayment of Ministry of Food and Agriculture (Mofa) Micro-Credits by Agricultural Producers in the Central Region of Ghana - Omega, Peter Kofi (University of Cape Coast, 2010)
The study examined the factors influencing the repayment of MOFA micro-credits in the Central Region of Ghana using a descriptive-correlation design. A multi-stage random sampling procedure was used to obtain data for the study. Chi-square tests at 5% level of significance showed that there was significant difference between the repayment of MOFA micro-credits and the demographic and socio-economic characteristics of clients. The F-values of 686.71 and 15.96 indicated that the micro-credit repayment models had good fit (p = 0.00) with an adjusted R2 of 0.999 and 0.896 for micro-credit clients and Agricultural Extension Agents perceptions on .MOFA micro-credit repayment respectively. The probability of MOFA micro-credit repayment is influenced mostly by stability in agricultural production, type of agricultural activity client engaged in, wealth status of client, household size of client, adequacy of credit, market opportunities for produce, repayment duration of credit, training for client, timely credit delivery, and supervision of credit use. It is recommended that MOFA micro-credits should be re-packaged with reasonable interest rates before delivery to the clients at the right time and with adequate credit repayment duration depending on production cycle. MOFA should target agricultural producers irrespective of age, sex, marital status, educational level, household size and wealth status with credit. Resource poor clients should be in groups for credit programmes. MOFA should train clients in agricultural activities to improve on their knowledge and skills. There should be regular supervision on credit allocation and use, while potential markets established within preferred areas for sale of produce.
xxii, 277p;, ill.